2016
DOI: 10.1111/crj.12507
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pulmonary rehabilitation on COPD exacerbation frequency per year

Abstract: Notwithstanding disease severity, PR treatment is reported to have positive effects on COPD patients in terms of perceived dyspnea, exercise capacity, arterial oxygenation, quality of life, anxiety and depression. This study found reduced number of emergency referrals and hospitalization among COPD patients with frequent exacerbations after PR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
0
17
0
1
Order By: Relevance
“…For this reason, PR is considered to be one of the most efficient nonpharmacological methods in the treatment of COPD patients (24). Changes in pulmonary functions after PR show variation, however, and there are studies reporting no change in pulmonary functions (25,26) as well as the studies reporting increased FEV 1 values after PR (27)(28)(29). In our study, there was a significant increase in FEV 1 values in the normal-weight and pre-obese patients, whereas the increase in obese patients was not significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, PR is considered to be one of the most efficient nonpharmacological methods in the treatment of COPD patients (24). Changes in pulmonary functions after PR show variation, however, and there are studies reporting no change in pulmonary functions (25,26) as well as the studies reporting increased FEV 1 values after PR (27)(28)(29). In our study, there was a significant increase in FEV 1 values in the normal-weight and pre-obese patients, whereas the increase in obese patients was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies demonstrated increased exercise capacity after PR (27)(28)(29). One study, which evaluated exercise capacity using an incremental shuttle walk test and endurance shuttle walk test by grouping the patients according to BMI found that the baseline ISWT value was significantly lower in obese patients and that there was a significant increase in all groups after PR, but the difference between the groups was not significant (31).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with a higher exacerbation risk score benefitted from reduced frequency of exacerbations and hospital admissions (61). In operative lung cancer patients even mild COPD is associated with significantly higher risk of postoperative complications than those with normal lung function (62).…”
Section: Which Patients Benefit From Rehabilitation Programs?mentioning
confidence: 99%
“…This highlights the well-recognized clinical reality that a substantial proportion of patients continue to exacerbate despite optimized medical therapy 1214. Given the association between acute exacerbations and both short and long-term outcomes,7,1517 there is an urgent need to advance pharmacotherapies targeting those with continued episodes 11,18,19…”
Section: Introductionmentioning
confidence: 99%